Peran Guru Bimbingan dan Konseling Dalam Menangani Kecanduan Game Online Pada Siswa SMA Negeri 10 Kota Kupang - Wesa, Paula Dolorosa De; Nalle, Andriani Paulin; Saba, Khetye Romelya; Abel, Rizky M.A (JURNAL BIMBINGAN KONSELING FLOBAMORA, 2024)
The problem of online game addiction that occurs at SMA Negeri 10 Kupang City really needs to be addressed, because it has a negative impact on students. To handle the level of student addiction to online games, assistance and guidance from various parties is needed, one of which is the role of Guidance and Counseling teachers. The aim of the research is to determine the role of Guidance and Counseling teachers in dealing with online game addiction among students at SMAN 10 Kota Kupang. This research uses qualitative research with data collection techniques of observation, interviews and documentation. This research was conducted at SMA Negeri 10 Kupang City. The informants for this research were 5 people consisting of 1 main informant and 4 additional informants. The technique for checking the validity of this research data uses source triangulation and technical triangulation. The results of the research show that the role of guidance and counseling teachers in dealing with online game addiction at SMA Negeri 10 Kupang city is to provide individual counseling services to students with problems, then make home visits to find out the factors that cause students to be addicted to online games, after that create a work program, namely following extracurricular activities and collaborating with school principals, parents and other teachers in order to control and supervise these students. This research also found the role of guidance and counseling teachers in preventing online game addiction. Counseling teachers provide classical guidance with information services to prevent students from becoming addicted to online games. From the research results it can be concluded that guidance and counseling teachers have an important role in dealing with online game addiction among students at SMA Negeri 10 Kupang city by collaborating with the school, being able to create varied programs and carrying out individual counseling and home visits as well as classical guidance.